Gadolinium-doped carbon dots with high-performance in dual-modal molecular imaging. Issue 21 (17th May 2021) - Wang, Le; Zhou, Wenjie; Yang, Dan; Zhe, Hu; Mei, Shiliang; Yuan, Jun; Zhang, Wanlu; Li, Hui; Fan, Hong; Xie, Fengxian; Guo, Ruiqian
Abstract : Carbon dots (CDs), possessing unexpected advantages of photostability, biocompatibility and low toxicity, can be used for fluorescence (FL) and magnetic resonance (MR) imaging. Abstract : Carbon dots (CDs), possessing unexpected advantages of photostability, biocompatibility and low toxicity, are regarded as novel nanomaterials in fluorescence (FL) imaging. Doping Gd element in CDs makes them have the ability to be used for magnetic resonance (MR) and FL imaging simultaneously. However, CDs reported before exhibit obvious defects like low photoluminescence (PL) quantum yield (QY) or biotoxicity. In this work, we use gadolinium meglumine, a material with relatively low biotoxicity, along with citric acid and diethylenetriamine to synthesize Gd-doped CDs (Gd-CDs) by a one-step hydrothermal method. The prepared Gd-CDs exhibit excitation-independent emission with a PL QY of 78.05% and a longitudinal relaxivity of 7.37 mM −1 S −1, which endows the composite with high-performance in MR/FL imaging. Meanwhile, the FL intensity of Gd-CDs remains stable in the presence of multiple amino acids, which indicates that the FL imaging effect should not be impacted significantly in microenvironments in vivo . In addition to the inconspicuous cytotoxicity, Gd-CDs could be used efficiently for dual-modal molecular imaging to detect diseases such as tumors in the early stages.